DQOBSR Protocol with QoS Provisioning for OBS Metro Rings. (12th September 2013) - Thachayani, M.; Nakkeeran, R.
Abstract : Optical burst switching (OBS) is the switching technology that enables optical internet with current technology. OBS networks are capable of operating with or without optical buffers and wavelength converters. Hence, medium access control (MAC) protocol plays an important role in resolving contention in such networks. Distributed Queue OBS Ring (DQOBSR) is one MAC protocol proposed for OBS ring networks. In this paper, the quality of service (QoS) provisioning scheme for DQOBSR protocol is presented. For the proposed protocol, service differentiation for different classes of traffic in terms of throughput and access delay is verified through simulation. A mathematical model is also presented for the computation of classwise mean access delay. The results obtained using the model are found to be in good agreement with the simulation results.